An impact assessment of machine learning risk forecasts on parole board decisions and recidivism - Berk, Richard (Journal of experimental criminology, 2017)
The Pennsylvania Board of Probation and Parole has begun using machine learning forecasts to help inform parole release decisions. In this paper, we evaluate the impact of the forecasts on those decisions and subsequent recidivism.